Gastroschisis in Europe – A Case‐malformed‐Control Study of Medication and Maternal Illness during Pregnancy as Risk Factors. Issue 6 (25th August 2017) - Given, Joanne E.; Loane, Maria; Garne, Ester; Nelen, Vera; Barisic, Ingeborg; Randrianaivo, Hanitra; Khoshnood, Babak; Wiesel, Awi; Rissmann, Anke; Lynch, Catherine; Neville, Amanda J.; Pierini, Anna; et al.
Abstract: Background: Gastroschisis, a congenital anomaly of the abdomen, is associated with young maternal age and has increased in prevalence in many countries. Maternal illness and medication exposure are among environmental risk factors implicated in its aetiology. Methods: A population‐based case‐malformed control study was conducted using data from 18 European congenital anomaly registries, with information on first trimester medication use, covering 8 million births 1995–2012. 1577 gastroschisis cases (of which 4% stillbirths, 11% terminations of pregnancy) were compared to 153 357 non‐chromosomal/monogenic controls. Literature review identified previous associations concerning maternal illness and medication exposure to be tested as signals. Logistic regression adjusted for maternal age group, registry, and time period was used to evaluate associations. Results: Comparing gastroschisis to other congenital anomalies, the data supported signals concerning maternal depression (aOR 2.52, 95% CI 1.45, 4.39), antidepressant use (aOR 2.03, 95% CI 1.22, 3.38), postnatal depression/psychosis following a previous pregnancy (aOR 8.32, 95% CI 2.56, 27.01), sexually transmitted infections (aOR 2.85, 95% CI 1.13, 7.24), topical antivirals (aOR 5.31, 95% CI 1.63, 17.33), and continuation of oral contraceptives in early pregnancy (aOR 2.17, 95% CI 1.13, 4.18). Exploratory analyses suggested associations with a wider range of maternal infections and medications, including tonsillitis and the expectorant bromhexine. Conclusions: While it is difficult to disentangle the effects of the medication and underlying indication, our results add to the evidence base on preventable risk factors for gastroschisis. These risk factors may contribute to the higher risk among young mothers, and geographical and temporal variation in prevalence.